Scenario development for D–T operation at JET. (12th June 2019) - Garzotti, L.; Challis, C.; Dumont, R.; Frigione, D.; Graves, J.; Lerche, E.; Mailloux, J.; Mantsinen, M.; Rimini, F.; Casson, F.; Czarnecka, A.; Eriksson, J.; et al.
Abstract: The JET exploitation plan foresees D–T operations in 2020 (DTE2). With respect to the first D–T campaign in 1997 (DTE1), when JET was equipped with a carbon wall, the experiments will be conducted in presence of a beryllium–tungsten ITER-like wall and will benefit from an extended and improved set of diagnostics and higher additional heating power (32 MW neutral beam injection  +  8 MW ion cyclotron resonance heating). There are several challenges presented by operations with the new wall: a general deterioration of the pedestal confinement; the risk of heavy impurity accumulation in the core, which, if not controlled, can cause the radiative collapse of the discharge; the requirement to protect the divertor from excessive heat loads, which may damage it permanently. Therefore, an intense activity of scenario development has been undertaken at JET during the last three years to overcome these difficulties and prepare the plasmas needed to demonstrate stationary high fusion performance and clear alpha particle effects. The paper describes the status and main achievements of this scenario development activity, both from an operational and plasma physics point of view.